2015
DOI: 10.14411/eje.2015.049
|View full text |Cite
|
Sign up to set email alerts
|

Measuring saproxylic beetle diversity in small and medium diameter dead wood: The "grab-and-go" method

Abstract: Abstract. Saproxylic organisms play a key role in a variety of forest ecosystem functions, which result in an increase in overall fo rest productivity and biodiversity. At present, dead wood is frequently removed from exploited forests. Estimating the effect of current forest management on biodiversity, and what gain in biodiversity would result from implementing restoration programs, requires the use of standardized sampling protocols. These protocols need to be suitable for use in different sampling areas an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…This is consistent with the findings of [25], who confirmed that bulky standing oaks are more valuable than thinner trees or even lying trunks. Some studies have also confirmed that the number of species increases with the dimensions of deadwood [73,74], and large specimens also host large species of beetles [75]. As the trunk diameter increases, the tree can offer a more diverse mosaic of microhabitats, such as large cavities or various stages of wood decomposition.…”
Section: Dimensions Of Heritage Treesmentioning
confidence: 92%
“…This is consistent with the findings of [25], who confirmed that bulky standing oaks are more valuable than thinner trees or even lying trunks. Some studies have also confirmed that the number of species increases with the dimensions of deadwood [73,74], and large specimens also host large species of beetles [75]. As the trunk diameter increases, the tree can offer a more diverse mosaic of microhabitats, such as large cavities or various stages of wood decomposition.…”
Section: Dimensions Of Heritage Treesmentioning
confidence: 92%
“…All of these factors combined have probably allowed the local survival of the species, but this needs to be confirmed by an adequate field survey using the methods (direct collecting, light traps, intercept traps, ex situ emergence traps) usually adopted in the monitoring of the closely related S. substriatus and other saproxylic Bostrichidae (cf. Mairhuber & Paill 2005;Paill 2005;Brustel et al 2013;Trizzino et al 2013;Redolfi De Zan et al 2014;Macagno et al 2015;Mifsud & Nardi 2016;Nardi et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Macagno et al. (2015) showed that the size of a bundle can influence the colonization rate of saproxylic species. We therefore determined the volume of each bundle by measuring the diameter and length of the six branches.…”
Section: Methodsmentioning
confidence: 99%